Ethiopia : Country Financial Accountability Assessment, Volume 2. Detailed Reports - World Bank (Washington, DC, 2013)
The CFAA examined the means by which the Federal Government of Ethiopia intends to improve the management of resources to enhance sustainable economic growth and reduce poverty. There are many challenges but the likelihood that Ethiopia will receive substantial assistance in the coming years means that, in order to maximize this opportunity, financial accountability issues and the exercise of fiduciary responsibilities in line with development goals are a priority. A key theme in the exercising of this fiduciary responsibility is to ensure that not only are the issues addressed at Federal level, but with the increasing devolution of fiscal responsibilities to 'Regions of Responsibility', that strengthening of financial accountability systems also occurs at the Regional level. Of particular emphasis will be the human capacity issues that decentralization initiatives have emphasized, which are in addition to technical considerations in systems for budgeting, accounting and financial reporting. Progress has been made in some areas over the last two years, particularly through the Expenditure Management Control Programme of the Ministry of Finance and Economic Development (MoFED) with the support of USAID. However, in the context of wider needs, there is still a considerable series of initiatives and tasks ahead for the Government. The CFAA was undertaken at a point in time when major transition was underway within the public expenditure management process in Ethiopia. Some of the issues identified are undoubtedly influenced by the fact that this change was taking place. The CFAA is presented in nine chapters. Following the introduction, Chapter 2 focuses on the work of the federal government and looks at public sector budgeting, accounting and reporting, and internal controls. Chapter 3 addresses public sector oversight arrangements and looks at the Office of the Federal Auditor General, Parliament and the newly established Federal Ethics and Anti-Corruption Commission. There is also a very brief examination of the issue of public access to information. Chapter 4 analyses the fiduciary risks at the federal level. With the increasing autonomy of regional governments, Chapter 5 focuses exclusively on this area using the assessments undertaken in four regions as a basis. This is followed by an analysis of the fiduciary risks at the regional level in Chapter 6. Chapter 7 deals with nongovernmental and community based organizations (NGOs/CBOs) and Chapter 8 the private sector. Finally, Chapter 9 addresses the skills and structural issues with regard to the accountancy profession in Ethiopia.